Policy styles in Germany: still searching for the rationalist consensus? - Zohlnhöfer, Reimut; Tosun, Jale (Policy styles and policy-making, 2018)
This chapter distinguishes policy styles along two dimensions. The first dimension is about how policymakers respond to the issues on the policy agenda. Do decision-makers anticipate societal problems, or do they react to them? The second dimension is about the relative autonomy of the state vis-à-vis other actors involved in policy-making and implementation. Do decision-makers seek to ensure consensus among the parties involved, or do they impose their decisions on the executing actors? Drawing on these two categories, in the original version of the volume edited by Jeremy Richardson (1982), Kenneth Dyson’s chapter on German policy styles claimed that decision-makers there would react to societal problems and seek to attain a rationalist consensus among all actors involved in policy-making and implementation. Considering the drastic modifications to the German political system since the time when Policy Styles in Western Europe was published that include, most importantly, the reunification of the country and changes to the dynamics of party competition and new coalition-formation patterns as well as increasing Europeanization and globalization, in this chapter we revisit the notion of the rationalist consensus for describing policy styles in Germany.
Gesehen am 27.06.2023